Pediatric paranasal sinuses—Development, growth, pathology, & functional endoscopic sinus surgery. Issue 6 (26th April 2022) - Lee, Sophie; Fernandez, Justin; Mirjalili, S. Ali; Kirkpatrick, Joshua
Abstract: The paranasal sinuses (maxillary, frontal, ethmoid, and sphenoid sinuses) are complex anatomical structures. The development and growth of these have been investigated utilizing a number of different methods ranging from cadaveric analysis to modern cross sectional imaging with 3D modeling. An understanding of normal pediatric paranasal sinus embryology and development enables us to better determine when pathology may be affecting the normal developmental process. Cystic fibrosis, chronic sinusitis, deviated nasal septum and cleft lip and palate are some of the conditions which have been shown to effect paranasal sinus development to varying degrees. Functional endoscopic sinus surgery (FESS) is becoming increasingly common and an understanding of sinus anatomy together with when periods of rapid growth occur during childhood is important clinically. Although concerns have been raised regarding the impact of FESS on facial growth, there is limited evidence of this in regards to either changes in anthropomorphic measurements or clinical assessments of symmetry post operatively.